Protease activated receptor 2 as a novel druggable target for the treatment of metabolic dysfunction-associated fatty liver disease and cancer - Villano, Gianmarco; Pontisso, Patrizia (Frontiers in Immunology, 2024)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is spreading worldwide, largely due to unhealthy lifestyles that contribute to the rise in diabetes, metabolic syndrome, and obesity. In this situation, the progression of injury to metabolic steatohepatitis can evolve to cirrhosis and, eventually, to hepatocellular carcinoma (HCC).It is well known that serine protease enzymes with different functions in cellular homeostasis, act as signaling molecules that regulate liver inflammation by activating the Protease-Activated Receptors (PARs) family members, expressed on the cellular plasma membrane. Among them, PAR2 plays a central role in the activation of signaling pathways in response to changes in the extracellular microenvironment. Experimental data have provided evidence that PAR2 is involved not only in the inflammatory response, but also in insulin resistance, lipid metabolism and cancer.The major aims of this narrative review are addressed to assess PAR2 involvement in inflammation, metabolism and liver disease progression and to explore possible therapeutic strategies, based on PAR2 inhibition, in order to prevent its biological effects in the context of MAFLD and cancer.